Análise biomecânica da corrida de velocidade em crianças com distintos níveis técnicos e da eficácia de uma intervenção didática - Rocha Junior, Ivon Chagas da (2006)
The purpose of this study was to identificate, describe and compare biomechanical variables of the sprinting technique, in the phase of maximal velocity, on children whith diferent levels of technique. Other goal was to make an experiment to test the effect of a didatic proceeding destinated to improve the subject s mastery in this task. The subject sample comprised two groups, one composed by children without any kind of classes of sprint technique, named Debutantes and other with a minimal experience of six months in learning and training the sprinting technique, named Initiates. The average age was 144,49 months. A 3D Kinematic analysis video system (Peak Motus System) was used to collect the biomechanical parameters, at a frequence of 180 Hz. The study was developed in a cinder track in good conditions, in two stages, the first with subjects performing two trials running in maximal velocity within any information and the second when the subjects had run two trials permanently facing an object placed in front of the course s axis. In each situation it were choosed the best trial in image s quality, to collect data. Data processing consisted of the analysis of 20 biomechanical variables referents to one running stride. The spacial and temporal variables were normalised in order to compare with other studies. The main results shows that Initiates had a higher level of mastery in the initial trial and the analysis of the second trial showed an increase of this diference. Statistical analysis had nt shown significante differences for variables in the comparison inter-trials. However technical and qualitative differences were found that are importante in regarding the sportive dimension, since in sprint there was little difference between performers in competition. Keywords: sprint technique; biomechanical analysis ; sport initiation